Nasal vaccination with attenuated Salmonella expressing VapA: TLR2 activation is not essential for protection against R. equi infection - Cardoso, Silvia Almeida; Oliveira, Aline Ferreira; Ruas, Luciana Pereira; Trevisani, Marcel Montels; Oliveira, Leandro Licursi De; Hanna, Ebert Seixas; Roque-Barreira, Maria Cristina; Soares, Sandro Gomes (Vaccine, 2013)
Virulent strains of Rhodococcus equi have a large plasmid of 80–90 kb, which encodes several virulence-associated proteins (Vap), including VapA, a lipoprotein highly associated with disease. We have previously demonstrated that oral immunisation with attenuated Salmonella enterica Typhimurium strain expressing the antigen VapA (STM VapA+) induces specific and long-term humoral and cellular immunity against R. equi. It was shown that VapA activates Toll-like receptor 2 (TLR2) on macrophages by establishing an interaction that ultimately favours immunity against R. equi infection. The purpose of this study was to evaluate the immune response triggered by nasal immunisation with STM VapA+ and to determine whether TLR2 supports the vaccine effect. We developed an optimised protocol for a single nasal immunisation that conferred protection against R. equi infection in mice, which was manifested by efficient R. equi clearance in challenged animals. Nasal vaccination with STM VapA+ has also induced protection in Tlr2−/− mice and mice with non-functional TLR4. Moreover, spleen cells of vaccinated mice augmented T-bet expression, as well as the production of IL-12, IFN-γ, nitric oxide and hydrogen peroxide. Notably, the population of CD4+ T cells with memory phenotype significantly increased in the spleens of vaccinated mice challenged 1 or 5 months after immunisation. In these animals, the spleen bacterial burden was also reduced. When similar experimental procedures were performed in TLR2 knockout mice, an increase in CD4+ T cells with memory phenotype was not observed. Consequently, we conclude that nasal vaccination with attenuated Salmonella expressing the R. equi virulence factor VapA confers long-lasting protection against experimental rhodoccocosis and that TLR2 engagement was not crucial to induce this protection but may be required for a long-term immune response.
Keywords: Rhodococcus equi; Vectored vaccine; VapA; Attenuated Salmonella; Toll-like receptors